Basic study on oxidation treatment of rice husk - Mohd Harizal, Abd Halim (Universiti Malaysia Perlis, 2008)
White husk ash suitable for use as reinforcement material for metal matrix composites. This rice husk based reinforcement material are material are prepared by first removing volatile constituent by heating the husks to a first relatively low temperature at 70°C for 24 hours. Fixed carbon is then oxidized by heating the husks to a second temperature above the separation temperature but below the crystallization temperature of the SiO2 in the husks, following by heat treatment at a third temperature above the crystallization temperature of the SiO2, to produce a uniform SiO2 crystal structure. The characteristics study of rice husk based SiO2 are determined by Optical Microscopy Analyser, Scanning Electron Microscopy (SEM), Energy Dispersive X-ray (EDX), and X-Ray Diffractometry (XRD).Based on the experimental work carried out, the result based on XRD analysis, the results suggested that optimum condition to get crystalline structure was achieved with heating temperature above 800°C and heating time between 2-4 hours.